2018
DOI: 10.1002/jcp.27300
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐128‐3p accelerates cardiovascular calcification and insulin resistance through ISL1‐dependent Wnt pathway in type 2 diabetes mellitus rats

Abstract: Vascular calcification is highly prevalent in patients with type 2 diabetes mellitus (T2DM), one of the most common chronic diseases with high morbidity and mortality.In recent years, microRNAs have been widely reported as potential biomarkers for the diagnosis and treatment of T2DM. We hypothesized that miR-128-3p is associated with cardiovascular calcification and insulin resistance (IR) in rats with T2DM by targeting ISL1 via the Wnt pathway. Microarray analysis was adopted to identify differentially expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…The expression of miR-128-3p is frequently observed in a variety of human diseases, including myocardial failure, diabetes, etc. [28,29]. It has been reported that the p38 MAPK signaling pathway is involved in the ALI inflammatory response and mediates the production of many cytokines, including IL-1β, TNF-α and IL-6 [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of miR-128-3p is frequently observed in a variety of human diseases, including myocardial failure, diabetes, etc. [28,29]. It has been reported that the p38 MAPK signaling pathway is involved in the ALI inflammatory response and mediates the production of many cytokines, including IL-1β, TNF-α and IL-6 [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of miR-128-3p is frequently observed in a variety of human diseases, including myocardial failure, diabetes, etc. [21,22]. It has been reported that the p38 MAPK signaling pathway is involved in the inflammatory response and mediates the production of many cytokines, including IL-1β, TNF-α and IL-6 in ARDS [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Through miRNA microarray analysis, Liu et al discovered that miR-32 increased RUNX2 expression and promoted VC in VSMCs by directly targeting phosphatase and tensin homolog (PTEN) [37], which was also found in cancer cells including colorectal cancer and MSCs [94]. MiR-128-3p has been shown to suppress inhibitors of Wnt/β-catenin and TGF-β signaling in cancer cells [95], leading to canonical Wnt activation and tumor resistance; Wang et al demonstrated that pancreatic tissue with miR-128-3p up-regulation also accelerated VC by intensifying Wnt/β-catenin signaling in diabetic animals, not VSMCs [48]. In endothelial cells, miR-135a-3p potently antagonizes angiogenesis and potentially serves as a tumor suppressor [96], while Gui et al additionally showed that VSMCs with miR-128-3p overexpression reduced Ca 2+ efflux and became calcified [17].…”
Section: Positive Vc-regulating Mirnasmentioning
confidence: 99%
“…Among them, 15 (40.5%) have been confirmed or are suspected to promote or aggravate VC in different scenarios, while 22 (59.5%) protect against VC formation or progression. Direct gene targets have been identified for 14 miRNAs with negative VC regulatory capacity, including miR-29a/29b [14], miR-29b-3p [34], miR-30b [16,47], miR-30c [16], miR-30e [25], miR-34b/34c [29,64], miR-125b [13,22] miR-133a [19], miR-135a [30], miR-182 [42], miR-204 [15,41,50], and miR-205 [21], while few direct targets have been identified for miRNAs with VC enhancement ability (miR-34a [39], miR-128-3p [48], and miR-135a-3p [17]). In the following sections, we describe the clinical features of each VC-regulating miRNA based on their propensity for positive or negative vascular influences.…”
Section: Mirnas In Vc: Positive and Negative Vc Regulatorsmentioning
confidence: 99%